Diphenyl diselenide protects against diabetic kidney disease through modulating gut microbiota dysbiosis in streptozotocin-induced diabetic rats - Wang, Xing; Long, Dongmei; Peng, Xingcan; Li, Jiaxuan; Zhou, Maoting; Wang, Yu; Hu, Xianghong (Frontiers in Pharmacology, 2024)
Diphenyl diselenide (DPDS) ameliorates nephropathy in streptozotocin (STZ)-induced type 1 diabetic rats by inhibiting oxidative stress and inflammatory reactions. However, it has not been clarified whether DPDS alleviates type 1 diabetic kidney disease (DKD) is related to the inhibition of extracellular matrix (ECM) production and the regulation of intestinal flora disorder. Here, the present study investigated the effects of DPDS on ECM generation in the kidney and intestinal microflora composition in feces. The rats were orally administered DPDS or metformin for eight weeks. As a result, DPDS and metformin improved the DKD in STZ rats, as evidenced by decreased blood glucose, BUN, urine volume, urine microalbumin, urinary β2 microglobulin, and improvement of renal pathological morphology. Furthermore, DPDS intervention markedly reduced the protein expression of α-SMA, COI Ⅳ, FN, and vimentin in the kidneys. Besides, DPDS not only improved dyslipidemia in STZ diabetic rats, but also enhanced the activities of antioxidant enzymes, decreased the level of MDA in serum and kidney, and regulated the expression of proteins related to the Nrf2/Keap1 signaling pathway in the kidney. Moreover, we found that DPDS could selectively improve the relative abundance of probiotics as well as the diversity of flora, thus ameliorating the intestinal microbial composition of the STZ rats, significantly regulating the intestinal microbial homeostasis. Overall, DPDS inhibited ECM production and improved renal pathological changes, which may be related to reducing oxidative stress damage in the kidney and improving intestinal flora imbalance, providing data support for the further development and application of DPDS in DKD.